2017
DOI: 10.1242/bio.026203
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage of timed cohorts ofTbx6-expressing cells in wild type andTbx6mutant embryos

Abstract: Tbx6 is a T-box transcription factor with multiple roles in embryonic development as evidenced by dramatic effects on mesoderm cell fate determination, left/right axis determination, and somite segmentation in mutant mice. The expression of Tbx6 is restricted to the primitive streak and presomitic mesoderm, but some of the phenotypic features of mutants are not easily explained by this expression pattern. We have used genetically-inducible fate mapping to trace the fate of Tbx6-expressing cells in wild-type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…Our analysis also revealed a contribution of Tbx6 reporter-positive cells to a number of tissues including posterior neural crest (Fig. S4) (Concepcion et al, 2017).…”
Section: Tbx6/sox2 Co-expression Marks Nmps In the Tail Budsupporting
confidence: 56%
“…Our analysis also revealed a contribution of Tbx6 reporter-positive cells to a number of tissues including posterior neural crest (Fig. S4) (Concepcion et al, 2017).…”
Section: Tbx6/sox2 Co-expression Marks Nmps In the Tail Budsupporting
confidence: 56%
“…This is a rare event in the Tbx6 rv/rv embryos that usually form at least one kidney. Abbreviations: pn, pronephros; ub, ureteric bud; g, gonad line to lineage trace cells that expressed Tbx6 revealing that timedinduction starting at e7.5-e8.5 resulted in labeled cells in the mesonephric tubules and metanephric primordia (Concepcion et al, 2017). This is perhaps not surprising since this would label cells in the PS, which are known to express Tbx6 (Chapman, Agulnik, Hancock, Silver, & Papaioannou, 1996).…”
Section: Discussionmentioning
confidence: 95%
“…In the chick, lineage‐tracing studies showed that PAM contributes to the renal stromal cells of the meso‐ and metanephros (Guillaume et al, ). More recent studies used a Tbx6‐Cre‐ERT2 line to lineage trace cells that expressed Tbx6 revealing that timed‐induction starting at e7.5–e8.5 resulted in labeled cells in the mesonephric tubules and metanephric primordia (Concepcion et al, ). This is perhaps not surprising since this would label cells in the PS, which are known to express Tbx6 (Chapman, Agulnik, Hancock, Silver, & Papaioannou, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on the T-box gene Tbx6 that is expressed between embryonic day (E) 6.5 and E13.5 in the primitive streak, the presomitic mesoderm and the tail bud, but not in the node, although node precursors do express the gene ( Concepcion et al, 2017 ). Tbx6 null mutants die around E9.5 with defects in anterior somite patterning, ectopic neural tubes and an enlarged tail bud ( Chapman et al, 1996 ; Chapman and Papaioannou, 1998 ; Takemoto et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%